ROLE OF GLYCATED HEMOGLOBIN IN THE DIAGNOSIS OF DIABETES MELLITUS: Glycated Hemoglobin - Khan, Sikandar Hayat; Khan, Farooq Ahmad; Sattar, Abdus; Hashim, Rizwan (Pakistan Armed Forces Medical Journal, 2008)
Objective: To evaluate glycated hemoglobin as a marker for diagnosis of diabetes mellitus.Design: Comparative cross-sectional studyPlace and Duration of Study: This study was carried out between July 2005 to April 2006 at department of chemical pathology and endocrinology, Armed Forces Institute of Pathology (AFIP) Rawalpindi.Subjects and Methods: Subjects (n=104) demonstrating impaired glucose regulation at the endocrine clinic of AFIP were selected. Forty seven age and sex matched normoglycemic healthy looking controls were also included in the study. Samples under complete medical fasting state were collected for glucose and glycated hemoglobin analysis, and then samples were collected at 1 hour and 2 hour for plasma glucose as part of oral glucose tolerance testing (OGTT). These subjects were later stratified to have all the disease ranges in terms of severity by 75 g OGTT results into following groups: Group-1: Controls, Group-2: Subjects with impaired fasting glucose (IFG), but became normoglycaemics on performing OGTT (Plasma glucose fasting result = 5.6 -6.9 mmol/L, but 2 h OGTT result < 7.8 mmol/L), Group-3: Subjects with impaired glucose tolerance (IGT) as per ADA recommendations (2 h OGTT result between 7.8-11.1 mmol/L), and Group-4: Subjects with diabetes mellitus as per American diabetic association (ADA) recommendations (2 h OGTT result >11.1 mmol/L). Receiver operating curve (ROC) curve analysis and diagnostic performance in terms of sensitivity, specificity, predictive values were used to evaluate the performance characteristic of glycated hemoglobin, in comparison with plasma glucose fasting and 1 hour OGTT results against 2 hour OGTT results taken as gold standard. Results: ROC curve analysis showed an area under the curve (AUC) of 0.722 for plasma glucose fasting, 0.607 for 1 hour OGTT and 0.564 for glycated hemoglobin. Moreover, the diagnostic performance as measured by sensitivity, specificity, predictive values and efficiency stood higher for plasma glucose fasting than glycated hemoglobin in the diagnosis of diabetes mellitus. Conclusion: Glycated hemoglobin, as determined by ion exchange resin chromatography is less useful for the diagnosis of diabetes mellitus than plasma glucose fasting. So the present approach for using plasma glucose fasting for diagnosing diabetes mellitus must remain in vogue.